Developing Developing an Adaptive E-Module Based on Cognitive Levels and Local Context to Improve Students Mathematics Computational Thinking Skills in Middle School - Bugis, Halima; Ratau, Asria (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study aims to enhance the computational thinking skills of middle school students using an adaptive e-module based on cognitive levels and local context. The research design employed is a pretest-posttest control group experimental design, with a sample consisting of 52 students divided into an experimental group of 26 students who used the adaptive e-module for learning, and a control group of 26 students who learned through conventional teaching methods. Data collection techniques included interviews, questionnaires, assessments of the adaptive e-module by teachers, and computational thinking skill tests in mathematics. The results of this development research include a teaching module based on cognitive levels and local wisdom, which met the feasibility criteria with a score of 48.5 out of a maximum score of 60, and media expert evaluation with a score of 31 out of a total of 40. Furthermore, the practicality test results showed 85% by students and 82.81% by teachers. The effectiveness test results indicated that the average computational thinking skill scores in the experimental class were 67.6 (pre-test) and 88.07 (post-test), while the control class scored 58.2 (pre-test) and 77.4 (post-test), leading to the rejection of the null hypothesis, which means there is a significant difference between the experimental group using the e-module and the control group